2022
DOI: 10.1186/s13287-022-02901-4
|View full text |Cite
|
Sign up to set email alerts
|

Clearance of senescent cells with ABT-263 improves biological functions of synovial mesenchymal stem cells from osteoarthritis patients

Abstract: Background Osteoarthritis (OA) is an age-related joint disease characterized by progressive cartilage loss. Synovial mesenchymal stem cells (MSCs) are anticipated as a cell source for OA treatment; however, synovial MSC preparations isolated from OA patients contain many senescent cells that inhibit cartilage regeneration through their senescence-associated secretory phenotype (SASP) and poor chondrogenic capacity. The aim of this study was to improve the biological function of OA synovial MSCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…There are many senescent cells in synovial MSC preparations obtained from patients with osteoarthritis (OA). Pretreatment with ABT-263 significantly reduced SA-β-gal-positive cells and Bcl-2 expression and improved the function of MSCs [164].…”
Section: Potential Mscs Rejuvenation Strategies For Agerelated Diseasesmentioning
confidence: 92%
“…There are many senescent cells in synovial MSC preparations obtained from patients with osteoarthritis (OA). Pretreatment with ABT-263 significantly reduced SA-β-gal-positive cells and Bcl-2 expression and improved the function of MSCs [164].…”
Section: Potential Mscs Rejuvenation Strategies For Agerelated Diseasesmentioning
confidence: 92%
“…At present, there are many studies on aging and osteoarthritis, ranging from the RNA level to the protein level. Based on existing studies (Liu et al, 2021), (Miura et al, 2022) , (Varela-Eirín et al, 2022), this study found that with the increase of age, the number of aging cells in articular cartilage increased, which promoted the occurrence of inflammatory aging-related secretory phenotype (SASP), and then led to an increase in the expression of inflammatory response-related genes and proteins. At the same time, it has been reported that osteoarthritis is related to bone metabolism.…”
Section: Introductionmentioning
confidence: 94%
“…ABT-263 also rejuvenated aged hematopoietic stem cells and muscle stem cells by clearing senescent cells ( Chang et al ., 2016 ). By binding the inhibitory domain of anti-apoptotic Bcl-2 and Bcl-xL, ABT-263 specifically eliminated both senescent muscle stem cells (MuSCs) and senescent bone marrow hematopoietic stem cells (HSCs) and eventually contributed to the amelioration or rejuvenation of MuSCs and HSCs in aged mice ( Miura et al ., 2022 ). In addition, ABT-263 cleared senescent foam cell macrophages in atherosclerotic lesions, preventing atherosclerosis progression in LDLR −/− mice ( Garrido et al ., 2022 ).…”
Section: Three Strategies To Target Senescent Cellsmentioning
confidence: 99%